A new quinic acid derivative with α-glucosidase inhibitory activity from the fruit of Gardenia jasminoides J.Ellis. Issue 11 (2nd June 2022) - Chen, Xu; Cao, Yan-gang; Ren, Ying-Jie; Wang, Meng-Na; Liu, Yan-Ling; He, Chen; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: A new quinic acid derivative (1 ) along with seven known compounds (2 –8 ) were isolated from the fruit of Gardenia jasminoides J.Ellis. All the structures of the isolated compounds were elucidated on the basis of the analysis of multiple spectroscopic data. The α -glucosidase inhibitory effects of the isolated compounds were investigated. The results showed that compounds 1 –3, 6, and 8 have moderate α -glucosidase inhibitory activities. Graphical Abstract: UF0001